Kallistatin as a Potential Biomarker in Polycystic Ovary Syndrome: A Prospective Cohort Study - Aslihan Yurtkal; Mujde Canday (Diagnostics, 2024)
Background: Polycystic Ovary Syndrome (PCOS) is a prevalent endocrine disorder with significant metabolic implications, including an increased risk of cardiovascular diseases and diabetes. Kallistatin, a serine proteinase inhibitor with anti-inflammatory and antioxidative properties, has been identified as a potential biomarker for PCOS due to its role in modulating inflammation and oxidative stress. Methods: This prospective cohort study was conducted at a university hospital’s gynecology clinic. It included 220 women diagnosed with PCOS and 220 healthy controls matched for age and body mass index. Kallistatin levels were quantitatively assessed using enzyme-linked immunosorbent assay (ELISA) techniques. Associations between kallistatin levels and clinical manifestations of PCOS, including hyperandrogenism and metabolic profiles, were examined. Results: Kallistatin levels were significantly lower in patients with PCOS (2.65 ± 1.84 ng/mL) compared to controls (6.12 ± 4.17 ng/mL; p < 0.001). A strong negative correlation existed between kallistatin levels and androgen concentrations (r = −0.782, p = 0.035). No significant associations were found between kallistatin levels and insulin resistance or lipid profiles. Conclusions: The findings indicate that reduced kallistatin levels are closely associated with PCOS and could serve as a promising biomarker for its diagnosis. The specific correlation with hyperandrogenism suggests that kallistatin could be particularly effective for identifying PCOS subtypes characterized by elevated androgen levels. This study supports the potential of kallistatin in improving diagnostic protocols for PCOS, facilitating earlier and more accurate detection, which is crucial for effective management and treatment.